COMPOSITION BASED ON THE SELECTED ARTISTS' PORTRAIT PAINTING STUDY - YU, WEI CHOW (unimas, 2017)
In this proposal, the study of composition used by Rembrandt and Caravaggio was carried out. The researcher will study about the application of composition used by the two an artists in making their paintings powerful. By using the combination of the two compositions used by these two anis[s, a personal artwork has been created.